Water temperature in the lakes of Northern Poland during the bathing season - Skowron, Rajmund (Bulletin of Geography. Physical Geography Series, 2018)
The study presents characteristics of the bathing season on the basis of stationary daily measurements of surface water temperature in the lakes in the period 1971-2015 conducted by the Institute of Meteorology and Water Management. These measurements are taken in the littoral zone (from bridges) of 28 lakes at 7:00 (6:00 GMT). In order to determine representativeness of these measurements, the author also documents the comparison of water temperature with its values at various points of the lake and its daily course. Stationary surface water temperature measurements provided the basis for the characteristics of the average, the earliest and the latest dates of the beginning and end of the bathing seasons, their duration and mean water temperatures in the summer months. Hence, a new parameter (tsum) is introduced to define the mean surface water temperature for the summer months (June, July and August), and compare water temperature in lakes over a larger area (the Baltic Sea catchment area). The most favorable conditions for bathing in Polish lakes are found in the western part of the Wielkopolskie Lakeland (lakelands: Łagowskie, Poznańskie, Slawskie and Myśliborskie) from the beginning of July to the end of August, when the surface water temperature in lakes generally exceeds 18°C. Furthermore, the best conditions for bathing in the water are from 10:00 to 18:00. When choosing a place to relax, holidaymakers should also consider bathing locations, infrastructure and safety conditions.